Sentencing disparity: An analysis of judicial consistency - Brantingham, Patricia L. (Journal of quantitative criminology, 1985)
This paper reports the results of an analysis of judicial disparity in the sentencing of persons represented by legal-aid lawyers. Because the socioeconomic characteristics of legal-aid clients are fairly uniform, the analysis of such cases made it possible to explore the influence of case facts, system factors, and the judicial disparity of the sentences given in relatively similar situations. The analysis finds that case facts and offender characteristics, particularly prior record, are good predictors of sentence type and excellent predictors of sentence length. While there was some indication of judicial inconsistency in sentence-type decisions, that is, unexplained variation from case to case, there was little indication of strong individual judicial bias across the cases used in the analysis.